The P450 oxidoreductase *28 SNP is associated with low initial tacrolimus exposure and increased dose requirements in CYP3A5-expressing renal recipients. (September 2011) - de Jonge, Hylke; Metalidis, Christoph; Naesens, Maarten; Lambrechts, Diether; Kuypers, Dirk RJ
Aim: Recently a SNP of the gene encoding P450 oxidoreductase ( POR*28 ; rs1057868C>T) has been associated with increased in vivo CYP3A activity using midazolam as a drug probe. Because tacrolimus is metabolized by CYP3A isoenzymes, this SNP might affect tacrolimus pharmacokinetics.Materials & methods: To test this hypothesis we performed a study in a cohort of 298 de novo renal allograft recipients stratified according to CYP3A5 genotype, which has a known impact on tacrolimus pharmacokinetics.Results: We found that in CYP3A5 expressers ( CYP3A5*1 allele carriers) receiving a standard loading dose of 0.2 mg/kg, POR*28T allele carriers had lower tacrolimus C0 levels in the first days post-transplantation and reached target C0 levels significantly later as compared with POR*28CC homozygous patients. The POR*28T allele carriers had significantly higher tacrolimus dose requirements throughout the first year. In CYP3A5 nonexpressers ( CYP3A5*3/*3 ) the POR*28 SNP did not affect tacrolimus pharmacokinetics.Conclusion: These data indicate that the POR*28 SNP is associated with additional increases in early tacrolimus dose-requirements in patients carrying a CYP3A5*1 allele. Original submitted 22 April 2011; Revision submitted 28 May 2011